Study of B Cell Repertoire in Patients With Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Feng, Jingjing; Fan, Siyuan; Sun, Yinwei; Zhang, Zhidong; Ren, Haitao; Li, Wenhan; Cui, Liying; Peng, Bin; Ren, Xiaotun; Zhang, Weihua; Guan, Hongzhi; Wang, Jing (Frontiers in Immunology, 2020)
Abstract Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most common antibody-mediated encephalitis. There are several studies on B cell repertoire of anti-NMDAR encephalitis in Caucasians. Here, the cerebrospinal fluid (CSF) samples of 12 Chinese patients with first-episode anti-NMDAR encephalitis were collected to investigate the B cell receptor (BCR) binding to NMDAR by single cell amplification of BCR and Sanger sequencing. BCR data of healthy persons, and of patients with anti-leucine-rich glioma inactivated 1 (anti-LGI1) encephalitis, multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD) from the public databases were used as control. A heavy chain common clone IGHV1-18*04, IGHD1-26*01/IGHD2-2*03/IGHD2-8*01, IGHJ3*02_(CDR3) ARVGSKYGFETFDI, was found in 11 of 12 enrolled patients, but not in the comparison data set. In addition, 4 shared clonotypes were found among these patients and three of them contained the common clone. This study also revealed that the antibody gene family usage preference between patients and healthy controls were different, while they had similar antibody mutation rate. Our findings may have potential clinical implications for the diagnosis of anti-NMDAR encephalitis.